Coastal Villages and Agricultural Villages; Implementation of a Self-Managed Project Management System in Developing Village Facilities and Infrastructure of Rural Development - Hasddin Hasddin; Fajar Saranani; Saemu Alwi (Journal of Global Innovations in Agricultural Sciences)
There is still controversy regarding the success of implementing a self-managed project management system in rural infrastructure development, including inconsistencies in the satisfaction (needs) of village communities as users in implementing development. This study evaluates the effectiveness of a self-managed project management system in rural infrastructure development, focusing on the relationship between user satisfaction and the performance of such projects in Southeast Sulawesi, Indonesia. The research, which involved 354 participants from a population of 708, uses secondary data obtained through questionnaires and analyzes it using the Customer Satisfaction Index (CSI) and SEM-AMOS techniques. The findings indicate that the community's satisfaction with infrastructure is only "quite satisfactory," highlighting the significant role of user satisfaction in the success of development projects. The study suggests that key stakeholders, including Village Heads and project managers, should collaborate to improve development management. The research also recommends that the central government refine the process of allocating village funds for infrastructure, ensuring that projects are aligned with community needs and deliver maximum benefits for local economic, social, and cultural activities. Keywords: Performance, CSI, project management, self-management, satisfaction, facilities and infrastructure, coastal villages.